Pembuatan Nanopartikel CaO dari Cangkang Telur Ayam Menggunakan Ekstrak Etanol Daun Salam (Syzygium polyanthum): Synthesis of CaO Nanoparticles from Chicken Eggshells Using Ethanol Extract of Bay Leaves (Syzygium polyanthum) - Mellida Yani; Gladys Ayu Paramita Kusumah Wardhani; Agus Taufiq (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Chicken  eggshell  waste  contributes  to  environmental because it have CaCO3 content. Calcium  carbonate  in chicken  eggshells  is  used  as  a  basic  material  in  the  synthesis  of  CaO  nanoparticles  through  a calcination process at 900oC. CaO nanoparticles have unique characteristics that make them are needed for various fields of application such as environment, materials, and biomedicine. In addition, the synthesis of these nanoparticles can reduce the use of hazardous and environmentally friendly chemicals. This method has been widely used as an alternative method, one of which  utilizes  secondary  metabolites found  in  ethanol extract of  bay  leaves as reducing  and stabilizing agents. This research was conducted with 3 volume variations of bay leaf extract with calcined eggshell base materials, namely 3:7, 5:5, and 7:3 (v/v) to determine the effect on the resulting particle   size.   Characterization   of   CaO   nanoparticles   using   UV-Vis,   FTIR,   and  SEM.   The nanoparticles obtained were in the form of white fine powder. The characterization results show the maximum absorption of CaO nanoparticles at λ 215 - 270 nm. Based on the FTIR spectra, Ca-O bonds can be identified in the three variations at 712 cm-1  dan 514 cm-1  and  874 cm-1  shows Ca-O-Ca bond. The resulting material has a flake shape and agglomeration morphology with an average particle size range of 43-498 nm.